Występowanie, wykorzystanie i ochrona ujęć wód podziemnych międzyrzecza Odry, Warty i Ilanki = Appearing, using and the protection of under-ground water intakes of the doab of the Odra, Warta and Ilanka - Rojna, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Portraying the hydrogeologic environment in the aspect of taking hold and protections of underground waters are a subject of the paper serving at targets existence-economic on the land of administrative districts Górzyca, Ośno Lubuskie and Słubice into the composition of the district of Słubicki. Paper with one's scope includes the number of problems having begun from the morphology of the land, the hydrography, the geological structure through the exploitation, the protection of underground water intakes and the change of the quality of the underground water in different period of times in individual towns.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); ochrona zasobów wodnych; eksploatacja zasobów wodnych; protection of water resources; exploitation of water resources